Immortalized stem cell-derived hepatocyte-like cells: An alternative model for studying dengue pathogenesis and therapy - Kongmanas, Kessiri; Punyadee, Nuntaya; Wasuworawong, Kasima; Songjaeng, Adisak; Prommool, Tanapan; Pewkliang, Yongyut; Manocheewa, Siriphan; Thiemmeca, Somchai; Sa-ngiamsuntorn, Khanit; Puttikhunt, Chunya; Faull, Kym Francis; Hongeng, Suradej; et al. (PLOS Neglected Tropical Diseases, 2020)
Author summary A model system resembling normal human liver cells is needed for advancement of hepatotropic infectious disease research. Here we show that immortalized cells (imHC) derived from human stem cells have a higher efficiency of DENV replication and a lower rate of cell death in response to DENV infection than the cancer cell-derived model systems currently used. The imHC also have active fat metabolism and respond well to anti-viral drug treatment, making them an attractive model for the initial stage of drug discovery and testing.